INDIA POST’S SERVICE QUALITY IMPACTS ON CUSTOMERS’ SATISFACTION AND LOYALTY (International Journal of Food and Nutritional Sciences, 2022)
During the time of the East India Company, the postal system of Tamilnadu was established.It began as a method for the East India Company and its employees to distribute mail. The system currently processes over 80 million pieces of mail per day. Even though India Post's postal services are more affordable, many individuals still prefer private couriers, just as many individuals prefer the services of other public and private banks. Still, many individuals are reluctant to visit the post office for a variety of services. The primary objective of this study is to investigate the connection between India Post's service quality, customer satisfaction, and customer loyalty. The most significant finding is that customer loyalty , satisfaction are correlates positively with service quality. In response, the postal service organises public education events, such as rallies and awareness camps, and distributes flyers and other promotional materials. To reach rural residents, advertisements for India Post's services must be made available in the local language as well.